Throat Carriage Rate and Antimicrobial Resistance of In Rural Children in Argentina - Gastón Delpech; Mónica Sparo; Beatriz Baldaccini; Gisela Pourcel; Sabina Lissarrague; Leonardo García Allende (Korean Society for Preventive Medicine, 2017)
Objectives The aim of this study was to determine the prevalence of asymptomatic carriers of group A β-hemolytic streptococci (GAS) in children living in a rural community and to investigate the association between episodes of acute pharyngitis and carrier status. Methods Throat swabs were collected from September to November 2013 among children 5-13 years of age from a rural community (Maria Ignacia-Vela, Argentina). The phenotypic characterization of isolates was performed by conventional tests. Antimicrobial susceptibility was assayed for penicillin, tetracycline, chloramphenicol, erythromycin, and clindamycin (disk diffusion). The minimum inhibitory concentration was determined for penicillin, cefotaxime, tetracycline, and erythromycin. Results The carriage of β-hemolytic streptococci was detected in 18.1% of participants, with Streptococcus pyogenes in 18 participants followed by S. dysgalactiae ssp. equisimilis in 5. The highest proportion of GAS was found in 8 to 10-year-old children. No significant association between the number of episodes of acute pharyngitis suffered in the last year and the carrier state was detected (p>0.05). Tetracycline resistance (55.5%) and macrolide-resistant phenotypes (11.1%) were observed. Resistance to penicillin, cefotaxime, or chloramphenicol was not expressed in any streptococcal isolate. Conclusions The present study demonstrated significant throat carriage of GAS and the presence of group C streptococci (S. dysgalactiae ssp. equisimilis) in an Argentinian rural population. These results point out the need for continuous surveillance of GAS and non-GAS carriage as well as of antimicrobial resistance in highly susceptible populations, such as school-aged rural children. An extended surveillance program including school-aged children from different cities should be considered to estimate the prevalence of GAS carriage in Argentina.